Changes in the incidence and predictors of human immunodeficiency virus-associated dementia in the era of highly active antiretroviral therapy. - Bhaskaran, K; Mussini, C; Antinori, A; Walker, A; Dorrucci, M; Sabin, C; Phillips, A; Porter, K (2008)
OBJECTIVE: Though effective anti-human immunodeficiency virus (HIV) therapies are now available, they have variable penetration into the brain. We therefore aimed to assess changes over calendar time in the risk for HIV-associated dementia (HIV-D), and factors associated with HIV-D risk. METHODS: Using Concerted Action on Seroconversion to AIDS and Death in Europe (CASCADE) data, we analyzed factors associated with time from HIV seroconversion to HIV-D using Cox models with time-updated covariates. The effect of duration of infection was explored using flexible parametric survival models. RESULTS: 222 of 15,380 seroconverters developed HIV-D. The incidence per 1,000 person-years was 6.49 pre-1997 (before highly active antiretroviral therapy was available), declining to 0.66 by 2003 to 2006. Compared with most recent CD4 count > or = 350 cells/mm3, the adjusted relative risk (95% confidence interval) of HIV-D was 3.47 (1.91-6.28), 10.19 (5.72-18.15), and 39.03 (22.96-66.36) at 200 to 349, 100 to 199, and 0 to 99 cells/mm3, respectively. In 2003 to 2006, older age at seroconversion (relative risk = 3.24 per 10-year increase [95% confidence interval, 2.00-5.24]) and previous acquired immune deficiency syndrome diagnosis (relative risk = 4.92 [95% confidence interval, 1.43-16.92]) were associated with HIV-D risk, independently of current CD4 count. HIV-D risk appeared to increase during chronic infection, by 48% at 10 years after seroconversion compared with the lowest risk at 1.8 years. INTERPRETATION: HIV-D incidence has reduced markedly since 1997. However, patients with low (<200 cells/mm3) or even intermediate (200-349 cells/mm3) CD4 counts, previous acquired immune deficiency syndrome diagnosis, longer HIV infection duration, and older age at seroconversion are at increased risk and should be closely monitored for neurocognitive disorders.